Surgical Site Infection by Corynebacterium macginleyi in a Patient with Neurofibromatosis Type 1 - Bruno Cacopardo; Stefania Stefani; Francesco Cardì; Carlo Cardì; Marilia Rita Pinzone; Giuseppe Nunnari (Case Reports in Infectious Diseases)
Corynebacterium (C.) macginleyi is a gram positive, lipophilic rod, usually considered a colonizer of skin and mucosal surfaces. Several reports have associated C. macginleyi with ocular infections, such as conjunctivitis and endophthalmitis. However, even if rare, extraocular infections from C. macginleyi may occur, especially among immunocompromised patients and patients with indwelling medical devices. We report herein the first case of surgical site infection by C. macginleyi after orthopaedic surgery for the correction of kyphoscoliosis in a patient with neurofibromatosis type 1. Our patient developed a nodular granulomatous lesion of about two centimetres along the surgical scar, at the level of C4-C5, with purulent discharge and formation of a fistulous tract. Cervical magnetic resonance imaging showed the presence of a two-centimetre fluid pocket in the subcutaneous tissue. Several swabs were collected from the borders of the lesion as well as from the exudate, with isolation of C. macginleyi. The isolate was susceptible to beta-lactams, cotrimoxazole, linezolid, and glycopeptides but resistant to quinolones, third-generation cephalosporins, and erythromycin. Two 30-day courses of antibiotic therapy with amoxicillin/clavulanate (1 g three times/day) and cotrimoxazole (800/160 mg twice a day) were administered, obtaining a complete healing of the lesion.